PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS, LEVERAGE, TANGIBLE ASSET TERHADAP CASH HOLDING PERUSAHAAN MANUFAKTUR - Laura Widjaja; Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to find out whether growth opportunity, profitability, leverage, and tangible asset affect cash holding. The sample selection method used is purposive sampling withthe number of selected samples was 60 manufacturing companies listed on the Indonesia StockExchange (IDX) for the period 2018-2020. This study used multiple regression analysis with EViews 12 and Microsoft Excel 2019 programs. The results of the t test showed leverage,tangible assets had a significant negative effect and profitability had a significant positive effect on cash holdings. While growth opportunity has no significant effect on cash holding. The implication in this research is that a company requires to manage cash well so that it can achieve an optimal cash holding level in carrying out its operational activities.